Colonization with 19F and other pneumococcal conjugate vaccine serotypes in children in St. Louis, Missouri, USA. Issue 34 (3rd August 2017) - McFarland, Michelle; Szasz, Taylor P.; Zhou, Julie Y.; Motley, Kara; Sivapalan, Janardan S.; Isaacson-Schmid, Megan; Todd, Elizabeth M.; Hogan, Patrick G.; Fritz, Stephanie A.; Burnham, Carey-Ann D.; Hoffmann, Steen; Morley, Sharon Celeste
Highlights: Prevalence of pneumococcal nasopharyngeal colonization of children 0–17 years old was 21.2%. Of 88 isolates, 16 were vaccine-type (11 were 19F), despite 87% vaccine coverage. Our results highlight the need for local surveillance of pneumococcal epidemiology. Abstract: Background: The epidemiology of nasopharyngeal (NP) pneumococcal carriage varies with geography and has changed in response to pneumococcal conjugate vaccine (PCV): a low prevalence (3% or less of colonizing isolates) of colonization by vaccine-type (VT) pneumococcal serotypes after PCV introduction has been reported. The primary goal of this study was to determine the VT serotype prevalence of NP pneumococcal colonization of children residing in the St. Louis, MO, USA metropolitan area following introduction of the 13-valent PCV in 2010. The secondary goal of this study was to identify characteristics associated with NP pneumococcal carriage of any serotype. Methods: Between July 2013 and April 2016, we enrolled 397 healthy children, aged 0–17 years, who required sedation for procedures or minor surgeries at St. Louis Children's Hospital. NP swabs were collected after sedation or anesthesia and cultured for pneumococcus. Vaccine records were obtained from primary care providers or from state immunization databases. Parents/guardians completed a questionnaire to provide demographics, past medical history and household characteristics. Results: Of the 88 pneumococcal isolates recovered from 84 colonized subjects (21.2% of all enrolled subjects; 95% CI 17.2–25.2%), 16 were VT. Eleven isolates were serotype 19F (12.5%), four (4.5%) were 6A and one (1.1%) was 19A. Prevalence of VT among colonizing isolates was thus 18.2% (CI 10.1–26.1%) in our cohort, despite complete PCV vaccination in 87% of colonized children. Factors associated with pneumococcal colonization by any serotype included younger age and daycare attendance. Conclusion: Children in St. Louis exhibit a higher prevalence of VT serotypes among pneumococcal carriage isolates than has been reported in other areas in the US, demonstrating the necessity of ongoing surveillance of local epidemiology and providing evidence that serotype 19F can remain prevalent in a pediatric population despite high vaccine uptake.